Low PD-1 mRNA Expression in Peripheral Blood of Childhood Leukemia - Aisyi, Mururul; Azhar, Muhammad Al; Dwijayanti, Fifi; Faujiah, Ulfa (Asian Pacific Journal of Cancer Biology, 2025)
Background: The expression of PD-1 has been linked to prognosis and response to immune checkpoint inhibitors in solid tumors, but less is known about their role in pediatric blood cancers. Therefore, we aimed to study the levels of PD-1 mRNA in children with leukemia and explore how they relate to clinical factors. Methods: Blood samples were collected from 15 children with leukemia and 11 healthy individuals. PD-1 mRNA expression was analyzed using real time PCR. Results: PD-1 mRNA expression was significantly lower in childhood leukemia patients (average DCT: 12.3±2.5) compared to healthy individuals (average DCT: 10.3±0.5) (p=0.011). PD-1 mRNA expression did not correlate with gender, age, diagnosis, remission status, down syndrome, hyperleukocytosis, infection, and outcome. Conclusion: Our findings indicated that mRNA expression of PD-1 was reduced in children with leukemia compared to healthy individuals and was not associated with all analyzed clinical factors. These results provide early insights into PD-1 expression in Indonesian pediatric leukemia patients.